Identifikasi Data Remote Sensing NDVI, LST DAN LULC Pada Manifestasi Panas Bumi Di Kabupaten Bondowoso - Linggar Ayu Octaviani; Bowo Eko Cahyono; Agus Suprianto (Postgraduate, University of Mataram, 2025)
The increasing energy demand in Indonesia encourages the exploration of alternative energy sources, including geothermal energy. Bondowoso Regency, particularly the Blawan area, holds significant geothermal potential that remains underutilized. This study analyzes the relationship between Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), and Land Use Land Cover (LULC) using Landsat 8 imagery processed through Google Earth Engine. Spatial data of LST, NDVI, and LULC were extracted, visualized, and interpreted to identify geothermal manifestation areas. The results show that geothermal manifestations are indicated by high LST values (above 35°C), low NDVI values (sparse vegetation), and specific land use patterns, especially in the northeastern part of Bondowoso. The integration of LST, NDVI, and LULC enables more accurate identification of geothermal potential. The study concludes that remote sensing-based analysis is effective for detecting geothermal manifestations and supports more optimal geothermal resource mapping, exploration, and management, contributing to the sustainable development of renewable energy in the region.